Representation of Indigeneity in Women’s Reproductivities in Sophie Mackintosh’s Blue Ticket - Sabrina Indah Kumala; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2025)
This research examines the representation of indigeneity in women's reproductivities in Sophie Mackintosh's Blue Ticket, focusing on how the patriarchal system controls women's bodies and identities. The novel depicts a dystopian society where women's reproductive fate is determined through a lottery system, reflecting the way state power shapes and marginalizes women's subjectivity. With a qualitative method and close reading approach, this study uses Simone de Beauvoir's existentialist feminism and Gayatri Spivak's postcolonial feminism to analyze the interrelationship between reproduction, indigeneity, and gender-based oppression. The research findings reveal that the main character, Calla, portrays resistance to a system that erases women's agency and authority over their bodies. Despite demonstrating an attempt at freedom, Calla must face the consequences of exclusion and violence. This representation shows that women's efforts to resist patriarchal structures are frequently undermined by the system that supports their dominance. This research concludes that Blue Ticket presents reproduction as a realm of conflict between identities shaped by the system and women's struggle to achieve an autonomous existence.